The Line of the Light: Painting backstage affective atmospheres. - Brennan, Emily Rose (Curtin University, 2024)
This project explores the embodied experience of the affective atmosphere of the backstage of the theatre, questioning how this site can be visually translated using oil painting. Through the analysis of the affective capabilities of painting, the phenomenology of acting processes, and atmospheres that reside in backstage interiors, I investigate how the lived-experience of backstage sites can contribute to paintings which register affective atmospheres linked to heightened energy, focused concentration, imaginative processes, and liminal sensations.